2014
DOI: 10.1088/0004-637x/794/2/102
|View full text |Cite
|
Sign up to set email alerts
|

NuSTARANDXMM-NEWTONOBSERVATIONS OF LUMINOUS, HEAVILY OBSCURED,WISE-SELECTED QUASARS ATZ∼ 2

Abstract: Peer-review status of attached le: eerEreviewed Citation for published item: ternD hF nd vnsuryD qFfF nd essefD FtF nd frndtD FxF nd elexnderD hFwF nd fllntyneD hFF nd flokovi¡ D wF nd fuerD pFiF nd fenfordD hF nd flinD eF nd foggsD FiF nd fridgeD gF nd frightmnD wF nd ghristensenD pFiF nd gomstriD eF nd grigD FF nd hel woroD eF nd iisenhrdtD FFwF nd qndhiD F nd qri0thD FvF nd rileyD gFtF nd rrrisonD pFeF nd rikoxD FgF nd trrettD FrF nd uossD wF nd vkeD F nd vwssD FwF nd vuoD fF nd siD gFEF nd rryD gFwF nd lto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 60 publications
(93 reference statements)
10
124
0
Order By: Relevance
“…Hot DOGs are characterised by high luminosity (L bol 10 47 erg/s) and large obscuration (up to AV ∼ 50 mag). Indeed, X-ray observations indicate that Hot DOGs are powered by heavily obscured, possibly Compton-thick AGN (Stern et al 2014;Piconcelli et al 2015). In our picture, high column densities and heavy extinction are expected at early times, with A V,sh ∼ 10 − 50 mag corresponding to timescales of a few ∼ 10 5 yr ( Figure 3).…”
Section: Observational Samplesmentioning
confidence: 55%
“…Hot DOGs are characterised by high luminosity (L bol 10 47 erg/s) and large obscuration (up to AV ∼ 50 mag). Indeed, X-ray observations indicate that Hot DOGs are powered by heavily obscured, possibly Compton-thick AGN (Stern et al 2014;Piconcelli et al 2015). In our picture, high column densities and heavy extinction are expected at early times, with A V,sh ∼ 10 − 50 mag corresponding to timescales of a few ∼ 10 5 yr ( Figure 3).…”
Section: Observational Samplesmentioning
confidence: 55%
“…5), and given that the mid-IR is largely independent of obscuration, a lower L X to L 5.8 ratio with respect to that observed for unobscured AGN suggests that the observed L X are affected by obscuration (e.g. Stern et al 2014). All the MIRO sources lie below these relations at values consistent with a heavily obscured absorber: the long-(short-) dashed line in Fig.…”
Section: Identikit Via Ancillary Datamentioning
confidence: 83%
“…More recently, R W 4 -, where W4 is the WISE flux at 22 μm, used in conjunction with nondetections in the WISE W1 (3.4 μm) and W2 bands (see Eisenhardt et al 2012;Wu et al 2012, andStern et al 2014 for a discussion of W W 1 2 -dropout sources), have been shown to identify extremely reddened Type 1 quasars (Yan et al 2013;Ross et al 2014), though such objects are rare and have a low space density. Additionally, infrared-only colors, such as Spitzer IRAC color selection Stern et al 2005;Donley et al 2012) and WISE W W 1 2 -color selection (Stern et al 2012;Assef et al 2013), have been adopted to identify both unobscured and obscured AGNs, including Type 2 AGNs locally and at highredshift and highluminosity (e.g., Lacy et al 2015), though these color selections work best at brighter fluxes since star-forming galaxy contamination becomes significant at fainter fluxes (Barmby et al 2006;Cardamone et al 2008;Donley et al 2008;Mateos 2012;Mendez et al 2013).…”
Section: Selecting Reddened Broad-lined Agnsmentioning
confidence: 99%